2014
DOI: 10.1371/journal.pone.0089678
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGFβ Signaling Increases Direct Conversion of Fibroblasts to Induced Cardiomyocytes

Abstract: Recent studies have been successful at utilizing ectopic expression of transcription factors to generate induced cardiomyocytes (iCMs) from fibroblasts, albeit at a low frequency in vitro. This work investigates the influence of small molecules that have been previously reported to improve differentiation to cardiomyocytes as well as reprogramming to iPSCs in conjunction with ectopic expression of the transcription factors Hand2, Nkx2.5, Gata4, Mef2C, and Tbx5 on the conversion to functional iCMs. We utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
170
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(189 citation statements)
references
References 42 publications
(110 reference statements)
15
170
1
3
Order By: Relevance
“…More recently, the same group used this reporter system to identify small molecules sufficient to enhance cardiac reprogramming and demonstrated that the transforming growth factor β (TGFβ) inhibitor, SB431542, was capable of increasing the conversion of both mouse embryonic fibroblasts and adult CFs into calcium transient + iCMs up to 5-fold. 89 Inhibition of TGFβ signaling at early in the reprogramming process led to the greatest increase in the conversion of fibroblasts to iCMs.…”
Section: Direct Reprogramming Into Cardiomyocytes By Different Factormentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the same group used this reporter system to identify small molecules sufficient to enhance cardiac reprogramming and demonstrated that the transforming growth factor β (TGFβ) inhibitor, SB431542, was capable of increasing the conversion of both mouse embryonic fibroblasts and adult CFs into calcium transient + iCMs up to 5-fold. 89 Inhibition of TGFβ signaling at early in the reprogramming process led to the greatest increase in the conversion of fibroblasts to iCMs.…”
Section: Direct Reprogramming Into Cardiomyocytes By Different Factormentioning
confidence: 99%
“…MiR-133 promoted cardiac induction by Snai1 suppression and silencing the fibroblast signature at the early stage. Given that TGFβ is an activator of Snai1, it is conceivable that TGFβ inhibitor-mediated cardiac reprogramming in mouse fibroblasts, reported by Ifkovits et al, 89 might be partly mediated through suppression of Snai1 and silencing fibroblast signatures. Intriguingly, this process is similar to the mesenchymal-to-epithelial transition process mediated through Snai1 suppression in iPSC generation.…”
Section: Direct Cardiac Reprogramming: Challenges and Future Directionsmentioning
confidence: 99%
“…8 Recently, it was reported that chemical compounds, including transforming growth factor β inhibitors, also promote cardiac reprogramming by suppressing fibroblast signatures. 35, 36 A major issue in direct reprogramming is that the efficiency of generating functional iCMs from fibroblasts was low. miRNAs, to GMT could result in reprogramming of human fibroblasts into iCMs.…”
Section: Progress Of Direct Cardiac Reprogrammingmentioning
confidence: 99%
“…They also found that GCaMP5 helps track the location of rare beating iCMs that represent fully reprogrammed cells. With the same method, Ifkovits et al 58 found that a small-molecule inhibitor of TGFβ, SB432542, increased reprogramming efficiency via GMTHN up to nearly 5-fold and generated more beating iCMs in mouse embryonic fibroblasts.…”
Section: Direct Cardiac Reprogramming In Vitromentioning
confidence: 99%